Control of Manganese Oxide Hybrid Structure through Electrodeposition and SILAR Techniques for Supercapacitor Electrode Applications - Kanisorn Klangvijit; Winadda Wongwiriyapan; Teerayut Uwanno; Michiko Obata; Masatsugu Fujishige; Kenji Takeuchi; Mayuree P. Reilly (My University, 2023)
Manganese oxide has been studied as a promising supercapacitor electrode due to its high theoretical capacitance, low cost, and environmental friendliness. Supercapacitor performance such as specific capacitance, resistance, and cycle life greatly depends on the morphology and crystal structure of manganese oxide. In this study, a Mn3O4 hybrid structure was successfully synthesized using electrodeposition and successive ionic layer adsorption and reaction (SILAR) techniques which are simple, cost-effective, and low-temperature wet chemical processes. It was found that Mn3O4 morphology is different depending on manganese precursors and synthesis techniques. Sea-grape-like and bird nest-like morphologies were obtained via the electrodeposition technique, while flower-like and nanoparticle morphologies were formed via the SILAR technique using manganese acetate and manganese sulfate as precursors, respectively. The hybrid structure of the nanoparticle-decorated bird nest-like heterostructure was prepared using manganese sulfate electrodeposition and subsequent SILAR deposition of manganese acetate. X-ray photoelectron spectroscopy confirmed the Mn3O4 formation. Electrochemical properties of manganese oxide hybrid structure were systematically studied with cyclic voltammetry and galvanostatic charge–discharge, showing the highest areal capacitance of 390 mF cm−2 at 0.1 mA cm−2 with series and charge transfer resistances down to 4.55 and 4.91 Ω in 1 M sodium sulfate electrolyte.
Keywords: Supercapacitor Materials and Fabrication